Determinants of poverty in Malaysia (1987 – 2017) / Ku Masliza Ku Chik @ Ku Kechik - Ku Chik @ Ku Kechik, Masliza (2020)
This study is undertaken to identify the determinants of poverty in Malaysia. The data employed in this study is from 1987 until 2017. This study is using poverty as dependent variable. Independent variables used in this study are remittances, inflation, economic growth and income inequality. The Dynamic Least Squares (DOLS) method has been used to explain the relationships. From the results, it is found that remittances and inflation are not statistically significant in determining the Malaysia’s poverty. Meanwhile, economic growth and income inequality are statistically significant in determining the Malaysia’s poverty.